Clinical team debriefing post-critical events: perceptions, benefits, and barriers among learners - Imperio, Michelle; Ireland, Kristin; Xu, Yiqing; Esteitie, Rania; Tan, Laren D.; Alismail, Abdullah (Frontiers in Medicine, 2024)
Background: Clinical team debriefings (TD) following critical events are pivotal in promoting team learning and enhancing patient outcomes. Despite their importance, perceptions and practices surrounding these debriefings remain under-researched. The purpose of this study was to explore learners' perceptions and experiences regarding debriefing practices, investigate correlations or discrepancies within those perceptions and experiences, and identify recommendations and potential practice improvements for clinical educators.Methods: This was a cross-sectional anonymous survey of healthcare professionals, including medical students, medical residents, nursing students, and respiratory therapy students.The survey was sent to respiratory therapy programs, nursing programs, internal and emergency medicine and pediatric residency programs in southern California and Michigan. The variables surveyed included demographics, team debriefing experience, code experience, TD perceptions, emotional status, cognitive load, and the benefits and barriers of conducting post-code TD. Emotional status and cognitive load were assessed using validated surveys by Paas et al and Barrett and Russell.Results: Of the 184 participants, 56% (n=104) were female. The mean cognitive load was 6.14 ± 1.6. A notable negative correlation was found between mental effort in recent real code experiences and emotional scales: "tense: calm" (r -.210; p = .018), "nervous: relaxed" (r = -.234; p = .008), and "stressed: serene" (r = -.258; p = .004). While 68.5% had attended a cardiopulmonary arrest event, only 34.9 had TD after their most recent code, and only 48.4% reported ever having a post-code TD.. Notably, nurses (75.4%) and attending physicians (73.8%) predominated these debriefings. Debriefings averaged 9.30 minutes (SD = 7.30) with a median of 6 minutes. The most recognized benefits were identifying areas of systems/process improvement and promoting teamwork and solidarity within the code team participants. The most commonly recognized barriers were lack of time and wanting a more senior person to initiate TD.The results of this study show a relatively low TD occurrence despite the high value learners attribute to TD. Addressing this inconsistency requires structured approaches, dedicated time, and an understanding of barriers. Recognizing the significant cognitive and emotional loads on learners further accentuates the need for structured post-event debriefings. Addressing these challenges with multi-disciplinary participation can enhance debriefing outcomes.